Polycristalline growth of zinc blende gallium arsenide layers by R.F. magnetron sputtering (Superficies y Vacío, 2014)
Zinc-blende GaAs layers were prepared on (100) Si and glass substrates by r.f. magnetron sputtering. The morphology of GaAs layers is analyzed by means of atomic force microscopy (AFM) and scanning electron microscopy (FE-SEM), to determine the sample topography and growth type. The compositional analysis was performed by means of energy dispersive X-ray spectroscopy (EDS), in order to obtain information of the atomic percentages of the elements and their spatial distribution in the samples. The optical properties of the layers are discussed from the results of UV-Vis absorption, and Photoacoustic spectroscopy (PAS). Finally, the Raman shift of the GaAs phonon modes are studied as function of the penetration depth of laser wavelength used to excite the sample on Raman microscopy.